On Results the Growth of Meromorphic Solutions of Algebraic Differential Equations (Communications in Mathematical Research, 2021)
In this paper, we give an estimate result of Gol'dberg's theorem concerning the growth of meromorphic solutions of algebraic differential equations by usingZalcman Lemma. It is an extending result of the corresponding theorem by Yuan etal. (Yuan W J, Xiao B, Zhang J J. The general theorem of Gol'dberg concerning thegrowth of meromorphic solutions of algebraic differential equations. Comput. Math.Appl., 2009, 58: 1788–1791). Meanwhile, we also take some examples to show thatour estimate is sharp.